Comprehensive view on chemotherapy-free management of acute myeloid leukemia by using venetoclax in combination with targeted and/or immune therapies - David Kegyes; Andrei Tat; Alin Stefan Vizitiu; Daiana Vazar-Tripon; Radu Ilie; Adrian Bogdan Tigu; Diana Cenariu; Anamaria Bancos; Sabina Iluta; Ciprian Jitaru; Madalina Nistor; Radu Tomai; et al. (Cell Death Discovery)
Abstract A hallmark of cancer biology is resistance to apoptosis. BCL-2 is an anti-apoptotic molecule that is being overexpressed in several myeloid diseases, such as acute myeloid leukemia and myelodysplastic syndromes, but also in several lymphoid cancers, such as acute lymphoblastic leukemia, chronic lymphocytic leukemia, non-Hodgkin lymphomas and multiple myeloma. Venetoclax (VEN) is a BCL-2 small molecule inhibitor. Data about its structure, biochemical characteristics and in vitro efficacy against several blood cancer cell lines were first reported in 2013. Shortly after, the first clinical trials reported that single-agent VEN provides no long-term survival benefits. In contrast, when used in combination, VEN led to significantly improved outcomes and eventually to its first US FDA approvals in 2018. As the modern approach to treating hematological malignancies are the chemotherapy-free regimen, in the current manuscript, we provide a comprehensive view on all available therapies that are considered to be chemotherapy-free, with a special emphasis on acute myeloid leukemia (AML), where phase I-III clinical trials have provided the most data.